Activity of lichia extract (Litchi chinensis Sonn.) on the biochemicals and histological parameters of diabetic rats - Brasil, Flávia de Fátima (2020)
Diabetes mellitus (DM) is a chronic non-communicable disease characterized as increased glucose, due to metabolic dysfunctions of carbohydrates, lipids and proteins. Along with the advancement of science the fruits and their by-products have been considered health promoters. In the present study the antihyperglycemic effect of the hydroethanolic extract of the peel and pulp of the fruits of Litchi chinensi (Lichia) in diabetic rats was evaluated. Wistar rats (250 to 300 g) with alloxan-induced DM 130 mg / kg were used. The animals were treated with extracts of Litchi chinensis 300 mg / kg for 75 days, by gavage. Blood glucose and biomarkers, such as triglycerides, cholesterol, renal and hepatic function were evaluated. Tissues such as liver, kidneys, heart and pancreas were removed for histological analysis. Diabetic rats treated with the peel of Litchi chinensis showed a significant reduction in fasting glycemia when compared to untreated rats. In addition to this beneficial action, rats treated both with the peel and the pulp, obtained reduction of the lipid levels, reducing the rates of triglycerides and cholesterol. Therefore, Litchi chinensis showed its benefit in the hypoglycemic and lipid-lowering effects, having therapeutic potential in the prevention and treatment of the complications of diabetes mellitus.